US Women's Perceptions and Acceptance of New Reproductive Health Technologies - Amber K. Worthington; Erin E. Burke; Talia N. Shirazi; Carly Leahy (Mary Ann Liebert, 2020)
Background: Women have faced persistent problems accessing reproductive health care. New applications of health technologies to reproductive health, specifically online fertility specialist consultations and reproductive hormone self-collection tests (SCTs), present unique opportunities to overcome these issues. This article uses the technology acceptance model to examine factors that influence women's intentions to use these new reproductive health technologies. Materials and Methods: Participants (n?=?327 US women) completed an online survey assessing perceptions related to both of these reproductive health technologies, including usefulness, ease of use, risk, trust, subjective norms, and personal responsibility, to learn about fertility. Results: Participants indicated high perceptions of usefulness, ease of use, and trust, as well as low perceptions of risk and subjective norms for both online fertility consultations (OFCs) and reproductive hormone SCTs. Women indicated low perceptions of responsibility to use OFCs, but high perceptions of responsibility to use reproductive hormone SCTs. Structural equation modeling indicated that intentions to use OFCs were predicted by usefulness, subjective norms, and responsibility; intentions to use reproductive hormone SCTs were predicted by usefulness, ease of use, subjective norms, and responsibility. Conclusions: Fertility specialist consultations and reproductive hormone testing can provide women with essential fertility information that facilitates informed reproductive decisions; however, these services have historically been difficult to access. Widespread uptake of new reproductive health technologies could promote positive advances in women's reproductive health outcomes.